Studies of the Control of Plasma Aldosterone Concentration in Normal Man: III. RESPONSE TO SODIUM CHLORIDE INFUSION - Williams, Gordon H. (1972)
The peripheral plasma levels of aldosterone, renin activity, potassium, sodium, corticosterone, and cortisol were measured in six normal subjects four times daily—10 a.m., 2 p.m., 5 p.m., 11 p.m.—on 3 consecutive days. A constant daytime activity program was maintained throughout the study. After 5 days on a 10 mEq sodium/100 mEq potassium isocaloric intake, the mean upright 10 a.m. plasma renin activity was 1773±186 ng/100 ml per 3 hr and the mean plasma aldosterone, 81±14 ng/100 ml. These two parameters fell continuously throughout the day parallel to the fall in plasma cortisol and corticosterone. In response to 2 liters of normal saline infused from 10 a.m. to 2 p.m. on 2 consecutive days, plasma aldosterone levels fell significantly to 13±5 ng/100 ml at 2 p.m. after the 1st day's infusion and to 6±1 ng/100 ml at 2 p.m. after the 2nd. Plasma renin activity demonstrated a parallel fall to 368±63 ng/100 ml per 3 hr and 189±27 ng/100 ml per 3 hr at 2 p.m. on the 1st and 2nd days, respectively. There was no significant alteration in plasma levels of cortisol, corticosterone, potassium, or sodium on the 2 days of sodium loading in comparison with the control day. In an additional study, five normal supine subjects received 500 ml saline/hr for 6 hr. As in the 2 day study, plasma aldosterone and renin activity had parallel decrements at 1, 2, 4, and 6 hr after the start of the saline infusion. From these studies, it is concluded that plasma renin activity is the dominant factor controlling plasma aldosterone when sodium-depleted normal subjects are acutely repleted.